Incidence, bacteriological profile and predictors of surgical site infections following limb amputation at Bugando medical centre and Sekou toure referral regional hospital, Mwanza, Tanzania - Haitham Hamudu; Helmut Nyawale; Vitus Silago; Mariam M. Mirambo; Phillipo L. Chalya; Stephen E. Mshana (Journal of Orthopaedic Surgery and Research)
Abstract Background Surgical site infections (SSIs) after limb amputations have been associated with increased patient morbidity, mortality and costs. This study aimed to determine the incidence, bacteriological profile and predictors of SSIs following limb amputation at Bugando Medical Centre (BMC) and Sekou Toure Regional Referral Hospital (SRRH). Methods The longitudinal study was conducted among patients undergoing limb amputations between March and July 2024 at BMC and SRRH. Pre-tested structured questionnaires were used to collect sociodemographic and clinical data. Clinical diagnosis of SSI was done using CDC criteria followed by collection of wound or pus swab for culture and susceptibility testing. Univariate and multivariate logistic regression modelling was done using STATA version 15.0 to assess associations between clinical variables and odds of SSI. Results A total of 120 patients with a median (IQR) age of 58 [43.5–66.5] years were enrolled. The indications for limb amputations included diabetic foot ulcers (50.8%,61/120), trauma (8.3%,10/120), malignancy (8.3%,10/120), gangrene (9.2%,11/120), peripheral vascular disease (16.7%,20/120) and congenital malformations (6.7%,8/120). The incidence of SSIs was (30%,36/120), with Escherichia coli (36.7%; 11/30) and Staphylococcus aureus (23%; 7/30) being the most frequently isolated pathogens. More than half of the Gram-negative isolates were resistant to third and fourth generations cephalosporins which were commonly used as prophylactic antibiotics in the study settings. Age above 65 years (OR = 0.21, 95% CI: 0.05–0.95, p = 0.043), smoking (OR = 14.3, 95% CI: 1.33-10.00, p = 0.027), ASA Class III (OR = 13.33, 95% CI: 2.82–63.14, p = 0.001), longer surgery duration (≥ 2 h) (OR = 4.09, 95% CI: 1.30-12.89, p = 0.016) and blood transfusion (OR = 2.4, 95% CI: 0.7-8.00, p = 0.02) were independently associated with SSIs. Conclusion About one third of the patients developed SSIs following limb amputation. Odds of SSIs were increased in patients with low age, smoking, high ASA score, prolonged surgery and who received blood transfusion. This highlighted the need to update the management protocol of limb amputation in relation to antibiotics prophylaxis among patients with increased risk of SSIs based on the local antimicrobial surveillance prevalence data.